2002
DOI: 10.1161/01.cir.0000021597.63026.65
|View full text |Cite
|
Sign up to set email alerts
|

Mild Renal Insufficiency Is Associated With Angiographic Coronary Artery Disease in Women

Abstract: Background-Mild renal insufficiency is associated with an increased risk for cardiovascular events in women with coronary artery disease (CAD). However, the relationship between mild renal insufficiency and atherosclerotic CAD in women is not known. Methods and Results-Women with chest pain who were referred for coronary angiography in the NHLBI Women's Ischemia Syndrome Evaluation (WISE) study underwent quantitative coronary angiography, blood measurements of creatinine, lipids, and homocysteine, and assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 15 publications
1
62
1
1
Order By: Relevance
“…[14] Moreover, other studies demonstrated that patients with CKD and C Cr <60 mL/min/1.73 m 2 BSA are also prone for nonrenal complications, mainly cardiovascular events. [23][24][25] This fact is very significant, considering that 1449 out of 4118 of the patients in present series were in these stages of CKD. Interestingly, although the incidence of AKI in both groups was similar, variables associated with the onset of AKI were different between the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…[14] Moreover, other studies demonstrated that patients with CKD and C Cr <60 mL/min/1.73 m 2 BSA are also prone for nonrenal complications, mainly cardiovascular events. [23][24][25] This fact is very significant, considering that 1449 out of 4118 of the patients in present series were in these stages of CKD. Interestingly, although the incidence of AKI in both groups was similar, variables associated with the onset of AKI were different between the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…4 In a study involving only women with chest pain, Reis et al found that plasma creatinine correlated with coronary artery disease score and with maximum coronary artery stenosis. 18 Chen et al, on the other hand, found that decreased renal function was associated with angiographic coronary artery disease in women but not in men. 5 In what concerns non-ST-elevation acute coronary syndrome, Gibson et al 19 and Fácila et al 20 have shown that mortality is associated with eGFR 19 and both with eGFR and creatinine as measured at admission.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in women with chest pain who undergo angiography, an elevated creatinine of 1.2 to 1.9 mg/dL is an independent predictor of significant angiographic coronary disease, as defined by a luminal narrowing of 50%. 136 The prevalence of LVH is also inversely related to the level of GFR. In one study, the prevalence of LVH, as measured by echocardiography, was 45%, 31%, and 27% in patients with creatinine clearance of Ͻ25, 25 to 50, and Ͼ50 mL/min, respectively.…”
Section: Reduced Gfrmentioning
confidence: 99%